Corporate Social Responsibility in the Opinion of Residents of Lubelskie Voivodship - Andrzej Soroka; Anna Mazurek-Kusiak (Barometr Regionalny)
This paper presents the opinions of residents of Lubelskie Voivodship on Corporate Social Responsibility of entrepreneurs operating within the Lublin region. The aim is to specify which actions performed by companies have the greatest influence on the perception of the company as being socially responsible as well as which factors determine the choice of employer. It has been shown that the most important activities that positively identify the employer as socially responsible are good treatment of employees, protection of the environment and provision of jobs in the local community. While choosing a new job, respondents take into consideration the honesty of the employer and the perspective for employee development through participation in training and courses. Also significant, however not as much as these, are: the company’s brand, environmental responsibility and a good corporate image. It has been shown that respondents from Lubelskie Voivodship have low awareness of ISO 26000 standards, which is related to the concept of Corporate Social Responsibility.